Development of Composite Biomaterial Based Dental Implants to Improve Osseointegration - Rith, Vicheka; Sok, Vann; Dara, Ravi (Journal of Biomedical and Techno Nanomaterials, 2024)
Dental implant technologies face significant challenges in achieving optimal osseointegration, critical for successful long-term patient outcomes. Traditional implant materials demonstrate limitations in biological performance, cellular interactions, and healing processes. Developing advanced biomaterial strategies capable of dynamically interacting with physiological environments represents crucial scientific innovation. Research objectives aimed to develop sophisticated composite biomaterial dental implants with enhanced osseointegration capabilities through innovative surface modifications and strategic ceramic reinforcement approaches. Experimental methodology employed comprehensive research design integrating materials science, cellular biology, and advanced computational modeling. Experimental protocols included precision biomaterial synthesis, nanoscale surface engineering, in vitro cellular response assessments, and sophisticated characterization techniques. Experimental results demonstrated statistically significant improvements in osseointegration rates, cellular attachment, and mechanical strength across developed composite biomaterial variants. Hierarchical surface modifications incorporating zirconia and hydroxyapatite reinforcements exhibited superior performance compared to traditional implant technologies. Conclusive findings validate innovative composite biomaterial approaches as transformative strategies for dental implant development, offering potential for accelerated healing, improved cellular interactions, and personalized medical interventions.